Relationship Between Knowledge Of Hypertension And Compliance With Chronic Disease Services Program (PROLANIS) - Nani Nur Khamidah; Dini Nurbeti Zen; Yoga Ginanjar (LPPM STIKes Muhammadiyah Ciamis, 2023)
Purpose : The purpose of this study was to determine the relationship between knowledge of hypertension and compliance with chronic disease service programs at the Wanareja II Community Health Center, Cilacap Regency. Methods: This type of quantitative research with a correlational research research design (correlational research). The sample in this study were all participants in the chronic disease program with hypertension as many as 124 people, with the sampling technique using random sampling technique. Bivariate analysis was performed using Kendal's tau test. Bivariate analysis using Kendal's tau obtained Sig. (2-tilled) of 0.000 is less than alpha 0.05 which means there is a significant relationship between knowledge of hypertension and compliance with chronic disease service programs. Results : There is a significant relationship between knowledge of hypertension and compliance with the chronic disease service program at the Wanareja II Health Center, Cilacap Regency. Conclusions: Health workers in these areas are expected to be more active in providing insight to the community, especially participants in chronic disease service programs.